2021
DOI: 10.3389/fimmu.2021.788985
|View full text |Cite
|
Sign up to set email alerts
|

ERAP2 Is Associated With Immune Infiltration and Predicts Favorable Prognosis in SqCLC

Abstract: BackgroundImmunotherapy has been proven effective among several human cancer types, including Squamous cell lung carcinoma (SqCLC). ERAP2 plays a pivotal role in peptide trimming of many immunological processes. However, the prognostic role of ERAP2 and its relationship with immune cell infiltration in SqCLC remains unclear.MethodsThe differential expression of ERAP2 was identified via GEO and TCGA databases. We calculated the impact of ERAP2 on clinical prognosis using the Kaplan-Meier plotter. TIMER was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…One potential explanation is environmental-and/or time-specific selection, whereby in times of high pathogen pressure there is strong evolutionary pressure to increase gene expression of ERAP2, but this is counterbalanced at other times by negative consequences (e.g., Crohn disease, type 1 diabetes). Previous literature has identified that changes in ERAP2 expression are associated with changes in survival from cancer, although one study identified increased survival 43 with increased ERAP2 expression, and the other decreased survival, 44 while there are known genetic associations such as psoriasis 45 and juvenile idiopathic arthritis 29 at this locus. Additionally, the association with birdshot chorioretinopathy is dependent upon an interaction with HLA, further complicating analyses.…”
Section: Discussionmentioning
confidence: 98%
“…One potential explanation is environmental-and/or time-specific selection, whereby in times of high pathogen pressure there is strong evolutionary pressure to increase gene expression of ERAP2, but this is counterbalanced at other times by negative consequences (e.g., Crohn disease, type 1 diabetes). Previous literature has identified that changes in ERAP2 expression are associated with changes in survival from cancer, although one study identified increased survival 43 with increased ERAP2 expression, and the other decreased survival, 44 while there are known genetic associations such as psoriasis 45 and juvenile idiopathic arthritis 29 at this locus. Additionally, the association with birdshot chorioretinopathy is dependent upon an interaction with HLA, further complicating analyses.…”
Section: Discussionmentioning
confidence: 98%
“…ERAP1 and ERAP2 are potential anti-cancer targets activating immune responses against malignant cancers by promoting T and NK cell-mediated cytotoxic responses [ 86 ]. One study noted that a higher expression of ERAP2 in the immunoreactive tumor microenvironment of Squamous-cell lung cancer (SqCLC) patients is correlated with high levels of immune markers and cells that include PD-L1, CD47, CD8+ TIL, CD68+ macrophages, and NK cells, which are all positive indicators for immunotherapy [ 87 ]. ERAP1 expression furthers the cancer progression, such as in cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…ERAP2 has previously been considered a homologue of placental leucine aminopeptidase/insulin-regulated aminopeptidase [23][24][25], but its function has not been thoroughly studied. Recent studies report that ERAP2 is an oncogenic gene, overexpressed in variant cancers, such as glioblastoma, choriocarcinoma and oral cavity squamous cell carcinoma (OSCC) [26][27][28][29]. ERAP2 overexpression has been reported to benefit cervical metastasis, resulting in a poor prognosis of OSCC [30].…”
Section: Discussionmentioning
confidence: 99%